Phytochemicals and bioactivities of three Macaranga species - Nur Zawani Abdul Razak, 1991-, author 522413; Farediah Ahmad, supervisor 330990; Fakulti Sains 8004 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Bibliography: p. 87-96.